Differences in Panoramic Mandibular Index value between male and female hypertension patients using panoramic radiography - Novi Tiara Lestari; Norlaila Sarifah; Didit Aspriyanto; Bayu Indra Sukmana; Isyana Erlita (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: This study is aimed to analyze the panoramic mandibular index value in male and female hypertensive patients using panoramic radiography. Materials and Methods: This research is a comparative analytic research with a purposive sampling technique. The study sample was hypertensive patients at Ulin Hospital, Banjarmasin from March to May 2023. Results: The results showed that there was no statistically significant difference through statistical data on the panoramic mandibular index value between men (0.27 ± 0.07) and women (0.26 ± 0.09), The age group that experienced a decrease in mandibular cortical thickness was most in the age group ≥ 65 years (0.22 ± 0.06). Conclusion: It is known that there is no significant difference in the panoramic mandibular index value between women and men.